Describing the heterotopic gastric mucosa (inlet patch) located in the esophagus with cases - Şengiz Erhan, Selma; Hallac, Sevinc; Ipin, Tugba; Gökden, Yasemin; Sensu, Sibel (Journal of Surgery and Medicine, 2020)
Aim: The inlet patch, also called as the heterotopic gastric mucosa, is often located in proximal esophagus and is generally asymptomatic. These lesions are rarely polypoid and mostly have a patchy pattern. In the literature, there are only few cases of inlet patches that show a malignant progression following a metaplasia- dysplasia- adenocarcinoma sequence. In our study, we aimed to present the endoscopic and morphological features of our case series. Methods: The study, which was conducted in two clinics, included the inlet patch cases diagnosed in esophagus biopsy materials between 2016 and 2019. The slides and the demographic data of the cases were re-analyzed. Results: Among 4190 cases whose esophageal biopsies were examined, 63 inlet patches (1.5%) were diagnosed. Thirty four cases were male and 29 were female. Age range was 16-82 years. The cases were mostly located in proximal esophagus and the size of the lesions ranged between 0.2-3.5 cm. One of the four cases with polypoid appearance was microscopically diagnosed as a hyperplastic polyp. The most common gastric type epithelium was the oxyntic type. Helicobacter pylori was observed in four cases, and intestinal metaplasia and low-grade dysplasia were observed in one. No malignancy was diagnosed in our series. Conclusion: Although benign, the inlet patch is significant due to its risk of progression to malignancy. Thus, obtaining biopsies from each lesion endoscopically considered as inlet patch is recommended. This will help determine the precise incidence of the inlet patch and more importantly, identify neoplasia earlier.